Intralaminar damage in polymer composites in the presence of finite fiber rotation: Part II – Numerical analysis and validation. (1st September 2016) - Eskandari, Sina; Andrade Pires, F.M.; Camanho, P.P.; Marques, A.T.
Abstract: In this paper the effects of fiber rotation inclusion in the continuum damage model are studied. Firstly, transverse compression case for unidirectional laminate composites is considered and the ability of the model to predict the final failure strength and fiber rotation angle for different initial fiber angles is analyzed using experimental data, and compared to the damage model excluding fiber rotation. Some damage analysis also carried out by means of X-ray images of damaged specimens. In addition, the ability of the models to be used for failure analysis of the thermoplastic matrix composites is evaluated. This type of composites reveals high level of fiber rotation, that makes them a good candidate to be investigated under this context. The study suggests the importance of fiber rotation inclusion in the damage analysis and highlights its advantages over not regarding it. Besides, it reveals the capability of the rotation considered model to be used for thermoplastic-based composites while the original damage model is not useful in this case.